Radial Migration Dynamics Is Modulated in a Laminar and Area-Specific Manner During Primate Corticogenesis - Cortay, Veronique; Delaunay, Delphine; Patti, Dorothée; Gautier, Elodie; Doerflinger, Nathalie; Giroud, Pascale; Knoblauch, Kenneth; Huissoud, Cyril; Kennedy, Henry; Dehay, Colette (Frontiers in Cell and Developmental Biology, 2020)
The orderly radial migration of cortical neurons from their birthplace in the germinal zones to their final destination in the cortical plate is a prerequisite for the functional assembly of microcircuits in the neocortex. Rodent and primate corticogenesis differ both quantitatively and qualitatively, particularly with respect to the generation of neurons of the supragranular layers. Marked areal differences in the outer subventricular zone progenitor cell density impact the radial glia scaffold compactness which is likely to induce areal differences in radial migration strategy. Here, we describe specific features of radial migration in the non-human primate, including the absence of the premigratory multipolar stage found in rodents. Ex vivo approaches in the embryonic macaque monkey visual cortex, show that migrating neurons destined for supragranular and infragranular layers exhibit significant differences in morphology and velocity. Migrating neurons destined for the supragranular layers show a more complex bipolar morphology and higher motility rates than do infragranular neurons. There are areal differences in the gross morphology and membrane growth behavior of the tip of the leading process. In the subplate compartment migrating neurons destined for the supragranular layers of presumptive area 17 exhibit radial constrained trajectories and leading processes with filopodia, which contrast with the meandering trajectories and leading processes capped by lamellipodia observed in the migrating neurons destined for presumptive area 18. Together these results present evidence that migrating neurons may exhibit autonomy and in addition show marked area-specific differences. We hypothesize that the low motility and high radial trajectory of area 17 migrating neurons contribute to the unique structural features of this area.